Essential microeconomics : principles, cases, problems - Mansfield, Edwin (New York : W. W. Norton, 1998)
This book is divided into five parts: Market demand and firm behavior; Perfect competition and monopoly; Oligopoly, monopolistic competition, and antitrust policy; The distribution of income; and Resource allocation and the Government.
Keywords: Microeconomics; Microeconomics